2013
DOI: 10.3324/haematol.2013.088161
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte count at diagnosis is a prognostic parameter in diffuse large B-cell lymphoma: results from a large multicenter study involving 1191 patients in the pre- and post-rituximab era

Abstract: ABSTRACTand prednisone (CHOP), CHOP-like, or third-generation anthracycline-containing regimens, with or without rituximab; 521 patients (51%) received the above therapies with rituximab as part of the regimen. Statistical analysisSurvival was assessed by Kaplan-Meier estimates 14 and compared by risk groups using the log-rank test and Cox proportional hazard analysis. 15 The proportional hazard assumption was verified graphically by means of scaled Schoenfeld residuals. 16 The effect size was reported as a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 26 publications
5
77
2
1
Order By: Relevance
“…Single-factor analysis or multi-factor analysis showed that AMC and ALC both were the independent poor prognostic factor and both of them adjusted to R-IPI may identify the high-risk patients in DLBCL and FL [15,17]. A multi-center study enrolled 1017 patients showed that AMC > 630 mm³ at diagnosis was a predictor to identify the high-risk patients in rituximab era [16]. During the period of R-CHOP treatment for patients with DLBCL, peripheral ALC/AMC ratio recovery may predict prognosis and ALC/AMC < 1.1 was an independent parameter of OS and PFS [29].…”
Section: Discussionmentioning
confidence: 99%
“…Single-factor analysis or multi-factor analysis showed that AMC and ALC both were the independent poor prognostic factor and both of them adjusted to R-IPI may identify the high-risk patients in DLBCL and FL [15,17]. A multi-center study enrolled 1017 patients showed that AMC > 630 mm³ at diagnosis was a predictor to identify the high-risk patients in rituximab era [16]. During the period of R-CHOP treatment for patients with DLBCL, peripheral ALC/AMC ratio recovery may predict prognosis and ALC/AMC < 1.1 was an independent parameter of OS and PFS [29].…”
Section: Discussionmentioning
confidence: 99%
“…The International Prognostic Index (IPI), which includes parameters such as age, stage, number of extranodal sites, performance status and serum lactate dehydrogenase (LDH) levels, is wellknown scoring system for risk stratification of DLBCL patients at diagnosis. However, the prognostic discriminating power of IPI alone diminished in the rituximab or immunochemotherapy era [5,6]. Gene-expression profiling, immunohistochemistry-based detection of prognostic biomarkers and early interim analysis with positron emission tomography (PET) had been explored as predictors that may identify high-risk patients [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, elevated peripheral blood monocyte counts have been shown to be an independent predictor of poor prognosis in patients with both non-Hodgkin and Hodgkin lymphoma. [5][6][7][8][9][10] Here, we investigated the relationship between peripheral blood monocytes at diagnosis and prognosis, focusing on CNS relapse in DLBCL.…”
Section: Introductionmentioning
confidence: 99%